Statistical modeling of joint reliability function using the copula method: Statistical modeling of joint reliability function using the copula method - Muradov, R.S.,; Ziyoitdinova, M. (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
Annotation. Data analysis goals may include estimation of the failure time distribution, and study of dependencies of failure times on study subject characteristics, exposures, or treatments, generically referred to as covariates. Failure time methods have application in many subject matter and research areas, including biomedical, behavioral, physical, and engineering sciences, and various industrial settings. In this paper discusses statistical modeling of joint reliability functions using the copula method.